Pediatric diagnostic medicine a collection of cases - White, Andrew, 1964 March 17-; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2022)
'Using a practical, case-based presentation, Pediatric Diagnostic Medicine helps you develop diagnostic skills, gain further knowledge through interesting cases, and improve critical thinking to reach a correct diagnosis. Dr. Andrew J. White, vice chair of education and director of the residency program at Washington University in St. Louis, presents dozens of real-world cases highlighted by full-color photographs. This unique case collection is an invaluable resource for pediatricians, residents, hospitalists, physician assistants, nurse practitioners, and anyone who provides care to children. Uses case-based teaching to develop higher-level medical thinking, based on James P. Keating's concept of pediatric diagnostic medicine. Teaches how to think about a patient's symptoms, dissect the issues, think backwards, and arrive at the correct diagnosis. Presents notable clinical cases starting with the presenting symptoms and then discussing vital signs, patient and family history, lab results, consults, differential diagnoses, and the ultimate diagnosis, finishing each case with teaching points. Includes additional relevant information on each case, such as why one diagnosis was chosen over another, or why certain tests were not run'--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Diagnostic Techniques and Procedures; Child; Signs and Symptoms; Adolescent; Infant; Case Reports; Pediatrics; Medicine